Pengaruh Pemberian Hadiah terhadap Motivasi Belajar Siswa Kelas VIII SMP Al-Falah Pondok Melati Mata Pelajaran IPS - Syahri, Ayu Fitri (FOCUS, 2024)
The purpose of this study was to find out about the effect of giving gifts on the learning motivation of class VIII students of SMP Al-Falah Pondok Melati in social studies for the 2022/2023 academic year. This type of research is quantitative research with experimental types. The subjects of this study were class VIII students with a total sample of 157 from 258 populations. Data collection techniques were taken using a questionnaire (questionnaire) with a Likert scale of 1-5. The instrument used was the attitude scale of giving gifts and social studies learning motivation. Testing the hypothesis of this research is to use descriptive analysis and simple regression analysis. From this study it can be seen that there is an effect of giving gifts on the learning motivation of class VIII students of SMP Al-Falah. From the statistical hypothesis it was concluded that there was an effect of giving gifts on learning motivation of 6.8% and rounded up to 7%. Judging from the simple ANOVA calculation, the p-value is less than 0.05